2001
DOI: 10.1007/pl00001888
|View full text |Cite
|
Sign up to set email alerts
|

Study of Carcinoembryonic Antigen Tissue Expression in Colorectal Cancer

Abstract: Aim:The aim of our study was to determine to what extent serial carcinoembryonic antigen (CEA) is helpful in detecting colorectal cancer recurrence. Second major objectives of this study were to evaluate tissue staining with CEA monoclonal antibody and its pattern of distribution in malignant tissue as regards its relation to prognostic value.Patients and Methods: 30 colorectal cancer patients undergoing clinically curative operations were studied. Primary tumors were evaluated for tissue CEA using immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In agreement with previous studies, the present study showed that both high-intensity t-CEA expression and the DC pattern were significantly associated with higher tumor recurrence rates 29 , 34 . Preoperative s-CEA concentration is also related to higher recurrence rates, as confirmed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies, the present study showed that both high-intensity t-CEA expression and the DC pattern were significantly associated with higher tumor recurrence rates 29 , 34 . Preoperative s-CEA concentration is also related to higher recurrence rates, as confirmed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that t-CEA expression intensity and pattern correlated significantly with preoperative s-CEA level. Although many previous studies have reported a lack of correlation between preoperative s-CEA levels and t-CEA expression 29 , 30 , 33 , 34 , one study confirmed this relationship 35 . These discrepancies may be due to differences in categorization of t-CEA expression patterns and intensities, and the small populations sizes (30–517 patients) in these studies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation